2014
DOI: 10.1111/mmi.12679
|View full text |Cite
|
Sign up to set email alerts
|

The novel globin protein fungoglobin is involved in low oxygen adaptation of Aspergillus fumigatus

Abstract: SummaryThe human pathogenic fungus Aspergillus fumigatus normally lives as a soil saprophyte. Its environment includes poorly oxygenated substrates that also occur during tissue invasive growth of the fungus in the human host. Up to now, few cellular factors have been identified that allow the fungus to efficiently adapt its energy metabolism to hypoxia. Here, we cultivated A. fumigatus in an O2-controlled fermenter and analysed its responses to O2 limitation on a minute timescale. Transcriptome sequencing rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…At present, genome-wide transcriptional profiling data of the hypoxic stress response are available from several filamentous ascomycetes: A. nidulans, A. oryzae, A. fumigatus, and Trichoderma reesei (Barker et al 2012;Bonaccorsi et al 2006;Hillmann et al 2014;Kroll et al 2014;Losada et al 2014;Masuo et al 2010;Terabayashi et al 2012). A somewhat smaller number of studies have been published on proteomic changes of A. nidulans and A. fumigatus during adaptation to low oxygen partial pressures (Barker et al 2012;Shimizu et al 2009;Vödisch et al 2011).…”
Section: Gene and Protein Expression During Hypoxiamentioning
confidence: 98%
See 1 more Smart Citation
“…At present, genome-wide transcriptional profiling data of the hypoxic stress response are available from several filamentous ascomycetes: A. nidulans, A. oryzae, A. fumigatus, and Trichoderma reesei (Barker et al 2012;Bonaccorsi et al 2006;Hillmann et al 2014;Kroll et al 2014;Losada et al 2014;Masuo et al 2010;Terabayashi et al 2012). A somewhat smaller number of studies have been published on proteomic changes of A. nidulans and A. fumigatus during adaptation to low oxygen partial pressures (Barker et al 2012;Shimizu et al 2009;Vödisch et al 2011).…”
Section: Gene and Protein Expression During Hypoxiamentioning
confidence: 98%
“…Several authors have reported that sustained mycelial growth of A. fumigatus requires O 2 levels around 0.1-0.2 % (Grahl et al , 2012bHall and Denning 1994;Hillmann et al 2014). Intriguingly, even fungi like the fermentative brewer's yeast Saccharomyces cerevisiae depend at least on some trace amounts of O 2 as substrate in anabolic pathways for the biosynthesis of sterols and unsaturated fatty acids (Rosenfeld et al 2003;Visser et al 1990).…”
mentioning
confidence: 94%
“…Such levels of hypoxia are normally no threat for many aspergilli, as trace oxygen levels are often sufficient to support their growth. To sustain electron flow during such conditions, A. fumigatus finetunes components of its respiratory machinery (7)(8)(9)(10). Enzymatic steps requiring molecular O 2 in heme or ergosterol biosynthesis are highly sensitive to hypoxia and are under the control of the sterol regulatory element binding proteins (SREBPs) SrbA and SrbB.…”
mentioning
confidence: 99%
“…Primers used for DNA amplification and DIG (digoxigenin) labeling of gene-specific probes are listed in Table S2 in the supplemental material. Semidry blotting, hybridization, and fluorescence-based detection were all performed as described previously (9).…”
mentioning
confidence: 99%
“…1). None of the transcriptomic data, taken from various growth conditions, indicated any transcription of ftpA or of other ftp cluster genes (19)(20)(21). Therefore, we could not a priori exclude a pseudogene scenario.…”
Section: Resultsmentioning
confidence: 99%